2018
DOI: 10.1007/s00330-018-5427-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of radiology reporting in a clinical cancer network: impact of an optimised multidisciplinary workflow

Abstract: • Undeveloped subspecialisation makes adherence to RECIST guidelines difficult in general hospitals. • A clinical cancer network provides opportunities to improve healthcare. • Optimised workflow, subspecialisation and structured reporting substantially improve request and report quality. • Good interdisciplinary communication between oncologists, radiologists and others contributes to quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…The benefits of the structured report are well-known in the literature and already demonstrated by some clinical implementation trials [21][22][23][24].…”
Section: Discussionmentioning
confidence: 84%
“…The benefits of the structured report are well-known in the literature and already demonstrated by some clinical implementation trials [21][22][23][24].…”
Section: Discussionmentioning
confidence: 84%
“…In terms of practical implementation, the successful integration of department-wide structured reporting programmes using a step-wise approach and an interdisciplinary agreement has been described before [29,30]. Olthof et al have demonstrated that interdisciplinary workflow optimisation including clarification of imaging request forms, subspecialisation of radiologists and structured reporting improves the quality of radiology reports in oncological patients [31]. Gormly reported on experiences with an oncological reporting concept that includes reporting templates with a layout comparable to SOR [32].…”
Section: Discussionmentioning
confidence: 99%
“…31 Organizations such as the ACR and the RSNA have established standardized templates for reporting imaging findings, 32,33 and accordingly, 6 countries in our survey reported using templates established by the RSNA or some other organization. Several studies [34][35][36] have examined the utility of structured reporting, particularly in its benefit to referring physicians. While structured reporting may lose some of the nuances of free-form reporting, it is less likely to use ambiguous terminology, relative to free-form reports, 36 and may avoid misinterpretation by referring physicians.…”
Section: Discussionmentioning
confidence: 99%